Contemplatio and speculatio: Are they synonyms or not? - Olszewski, Mikolaj (2016)
As an introduction to this text, I would like to present a short comment made by an anonymous author to William’s of Ware thesis claiming that theology is a contemplative science. The term contemplativus is understood by William as the third element enlarging the Aristotelian distinction of sciences into practical and speculative, the element different from speculativus and practicus; The argument given by the commentator of William’s work states clearly the synonymy of contemplatio and speculatio because of the similarity of their basic dictionary meanings. He adds that such understanding of these terms was shared also by St. Augustinus, whose terminology was very influential on Latin used by medieval scholars.